Natural rubber as a renewable and sustainable bio-modifier for pavement applications: a review - Ansari, Anwaar Hazoor; Mohd Jakarni, Fauzan; Muniandy, Ratnasamy; Hassim, Salihudin; Elahi, Zafreen (Elsevier, 2021)
The increasing demand for non-renewable resources such as bitumen is a significant problem in the pavement industry. Flexible pavement primarily relies on and consumes a large quantity of bitumen, which has become a significant problem in terms of environmental sustainability and economic standpoints. Hence, researchers strive to explore alternative solutions such as bitumen modifiers to prolong the lifespan of flexible pavements. One such modifier is natural rubber (NR), and it has exhibited some beneficial effects for bitumen and asphalt mixtures. However, its adoption as a modifier in the pavement industry is constrained. Hence, the main objective of this review is to analyse the literature in depth to reveal the possibilities of alternative uses of NR as a modifier in the pavement industry. NR in the forms of latex and cup lump was observed to improve the physical, rheological, and mechanical performance of bitumen. The uncross-linked polymer of fresh NR can easily swell and be absorbed by bitumen. In addition, the effect of blending variables is interdependent on the physical properties of the modified bitumen. However, NR decreases the workability of the asphalt mixture, which can be compensated for by warm mix additives. The optimum content of NR for bitumen to improve pavement performance is 4–6 wt.%. Meanwhile, NR absorbs 24.9 kg of CO2 to produce 1 kg of NR latex. This paper also discusses improved field condition indicators of NR-modified pavements. Finally, recommendations for future research and development are provided to promote the utilisation of NR in the forthcoming sustainable pavement industry.